SISTEM INFORMASI GEOGRAFIS PEMETAAN LOKASI PANTI ASUHAN DI KOTA MEDAN - Angga Kurniawan; Suendri Suendri; Triase Triase (UIN Sumatera Utara Medan, 2019)
The orphanage is a social welfare institution that has the responsibility to provide services to neglected children, the poor and orphans. Medan City Social Service as a place for social welfare institutions for orphanages in fact has not been able to manage the information optimally. In addition, the development of the orphanage is considered slow because of the lack of information about the location and needs of the orphanage that is presented to the public. The information is limited to brochure advertisements posted on the edge of the city of Medan. Therefore, we need a Geographic Information System (GIS) that is able to manage these data to be more effective and efficient. The application of the system uses the Waterfall development method, built using the PHP programming language, the Google Maps API as a map display and Bootstrap as an interface processor to make it look more attractive and responsive. Geographical Information System Mapping Orphanage Locations in Medan City presents spatial and non-spatial information about 19 Islamic orphanages in the city of Medan.